Function of the human cerebellum in timing and auditory-motor synchronisation - Zeni, Silvia (2020)
This thesis is divided into two main parts: introduction and experimental research. Chapter 1 and Chapter 2 in the introduction provide a theoretical background for the experimental research presented in Chapters 4–6. Chapter 3 includes a description of the general methods, set-up and measures used in the experimental research.